Association between plasma big endothelin-1 level and the severity of coronary artery disease in patients with non-ST segment-elevated myocardial infarction. (14th October 2021) - Lyu, S; Zhu, J; Yu, L; Yang, Y
Abstract: Background: This study aimed to evaluate the association between plasma big endothelin-1 (ET-1) level and the severity of coronary artery disease assessed by the SYNTAX score (SS) in patient with non-ST segment-elevated myocardial infarction (NSTEMI). Methods: A total of 766 patients with NSTEMI undergoing coronary angiography were recruited. Patients were divided into divided into three groups: low SS (SS ≤22), intermediate SS (23–32) and high SS group (SS >32). Spearman correlation, smooth curve fitting, logistic regression and Receiver operating characteristic (ROC) curve analysis were performed to evaluated the association between plasma big ET-1 level and the SS. Results: There was a significant correlation between the big ET-1 and the SS (r=0.378, p<0.001). Smoothing curve indicated a positive correlation between plasma big ET-1 level and the SS, after adjustment for potential confounders. The ROC curve analysis showed that the area under the curve was 0.695 (0.661–0.727) and the optimal cutoff of plasma big ET-1 level were 0.35pmol/l, with a sensitivity of 68.9% and a specificity of 62.9%. Logistic regression showed that elevated big ET-1 was an independent predictor of intermediate-high SS in patients with NSTEMI, no matter entered as a continuous variable [OR (95% CI): 1.110 (1.053–1.170), p<0.001] or as a categorical variable [OR (95% CI): 2.873 (2.016–4.094), p<0.001]. The association between big ET-1 and intermediate-high SS was consistent across subgroups without significant interactions. Conclusion: In patients presenting with NSTEMI, plasma big ET-1 level was significantly correlated with the SS. Elevated plasma big ET-1 level was an independent predictor for intermediate-high SS. Funding Acknowledgement: Type of funding sources: None.